INDIKASI MANAJEMEN LABA OLEH CHIEF EXECUTIVE OFFICER (CEO) BARU PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI PASAR MODAL INDONESIA - WIRAWAN YASA, GERIANTA; NOVIALY, YULIA (Jurnal Ilmiah Akuntansi dan Bisnis, 2012)
One of motivations of earnings management is the CEOs turnover. The increase of CEOs turnover has placed CEOs at high risk position, so the earnings management is being held to show the good performance of management. The purposes of this research are to test whether new CEO would like to practice earnings management and to test how firm size and auditor’s reputation influence earnings management. Sample comprises manufacturing companies that changed CEO during 2000-2008 and listed on the Indonesia Stock Exchanges. Earnings management is measured by discretionary accrual (DA), calculated using modified Jones Model. The hypotheses of this research are tested using Independent Samples t-Test and multiple regressions. The result shows that there is an indication of earnings management done by new CEOs. Futher analysis result shows that the type of earnings management that had been done is income decreasing. Earnings management is influenced negatively and significantly by firm size, but it’s not influenced by auditor’s reputations.
Keywords: CEOs turnover, earnings management, firm size, auditor’s reputation